(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates digital banking concepts and customer satisfaction, analyzing the purpose and reasons for choosing digital banking services. Data collection involved survey questions and answers from 100 users in the Kanyakumari district. Results were presented using percentage, chi-square, and F test statistical methods. The study aims to evaluate customer satisfaction with online banking services and identify issues they encounter. The findings will help businesses improve their digital banking offerings and improve customer satisfaction.